2013
DOI: 10.1111/1756-185x.12155
|View full text |Cite
|
Sign up to set email alerts
|

Serum Leptin in Egyptian patients with fibromyalgia syndrome: relation to disease severity

Abstract: We found a significant decrease in serum leptin in FMS patients compared to controls and this decrease correlated with disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Serum levels of leptin, a hormone with a role in energy expenditure, fat regulation, and suppression of hunger, were measured in FM patients. [34][35][36] Only 1 study demonstrated lower leptin levels versus controls, which correlated with symptom severity. 34 Obesity in FM is associated with the same variables as in the general population, including lack of exercise, history of physical and sexual abuse, depression, medical comorbidities, hypothyroidism, the number of musculoskeletal surgeries, and the number of medications taken for FM.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Serum levels of leptin, a hormone with a role in energy expenditure, fat regulation, and suppression of hunger, were measured in FM patients. [34][35][36] Only 1 study demonstrated lower leptin levels versus controls, which correlated with symptom severity. 34 Obesity in FM is associated with the same variables as in the general population, including lack of exercise, history of physical and sexual abuse, depression, medical comorbidities, hypothyroidism, the number of musculoskeletal surgeries, and the number of medications taken for FM.…”
Section: Discussionmentioning
confidence: 94%
“…Studies of obesity in the general population show that it is associated with medical comorbidities, 37 psychiatric pharmacotherapy, 38 depression, poor physical function, 34 and sexual and physical abuse. 39 To our knowledge, the relationship we observed between BMI and the number of medical comorbidities has not been previously reported in an FM cohort, although it has been demonstrated in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…However, such study failed to adjust the leptin levels by fat mass or stratify them by BMI (30). These authors demonstrated that leptin levels were significantly lower in patients with fibromyalgia than in controls.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreas and fatty tissue appear to be influential among the mechanisms that regulate appetite, the central nervous system, the gastrointestinal system (GIS), several anorexigenic and orexigenic peptides, and hormonal mediators released from the adrenals (1)(2)(3)(4)(5). Particular emphasis is being put on the leptin and ghrelin system in the pathophysiology of many diseases that affect appetite (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%